Continuous improvement of injection moulding using Six Sigma: case study. (11th June 2019) - Maged, Ahmed; Haridy, Salah; Kaytbay, Saleh; Bhuiyan, Nadia
Plastic injection moulding is considered as one of the very challenging processes to obtain output with a good quality and low cost. This paper presents a case study of the deployment of Six Sigma in plastic injection moulding to improve the quality of the final product by eliminating major defects occurred using cost effective methods. The main objective is to identify the major quality problems and to eliminate root causes by adopting Six Sigma define, measure, analyse, improve and control (DMAIC) methodology. The proposed Six Sigma approach effectively integrates quantitative and qualitative tools such as statistical process control (SPC) charts, Pareto chart, histogram, Ishikawa diagram, measurement system analysis, hypothesis test and checklist to achieve the desired goal. The results reveal that the implementation of the proposed Six Sigma approach can reduce the rejection rate significantly. It is found that the quality of the final products is substantially improved in terms of sigma level which increased from 4.06 to 4.5 and the cost of poor quality (COPQ) is reduced by 45%.